Medicine in the Sport of Horse Racing. Issue 9 (September 2020) - Ryan, Kelly D.; Brodine, Joseph; Pothast, Jason; McGoldrick, Adrian
Abstract : Abstract: Horseracing is among the most popular and increasingly lucrative industry sports in the nation. The average jockey must control a thoroughbred horse 10 times their weight that may act unpredictably whether at rest or full gallop resulting in falls, kicks, or even biting injuries. Despite the risks, jockeys do not have access to the same quality of medical care that is standard in similarly profitable sports organizations. Beyond the mental and physical demands of training and performance endured by any professional athlete, jockeys are confronted with health challenges unique to their sport. In this review of the literature, we aim to educate sports medicine physicians regarding the underlying causes of injuries, describe injury management, and make recommendations for appropriate preventive strategies. Overall, there is a void of literature, and so our authors offer expert opinion and encourage others to get involved in making this a safer sport.